2012 North American Power Symposium (NAPS) 2012
DOI: 10.1109/naps.2012.6336326
|View full text |Cite
|
Sign up to set email alerts
|

Targeted conversion of AC lines to DC lines for improved power system dispatch

Abstract: In this paper the concept of targeted conversion of AC lines to DC lines is proposed for improved securityconstrained economic dispatch by incorporating the converted line into the formulation to improve flow pattern control and relieve flow constraints on both the converted line and the remaining AC system. The proposed model treats the flow on the converted line as an independent control variable for the operator to utilize. It is shown that the introduction of this additional control variable significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…To this end, the conversion of AC lines to high-voltage direct current (HVDC) lines is a possible option [5]- [8]. HVDC lines feature a controllable power flow and provide dynamic voltage support at the terminals [9], which can further enhance the capacity of the connected AC grid [9], [10] and renders it particularly appealing from a technological point of view.…”
Section: Introductionmentioning
confidence: 99%
“…To this end, the conversion of AC lines to high-voltage direct current (HVDC) lines is a possible option [5]- [8]. HVDC lines feature a controllable power flow and provide dynamic voltage support at the terminals [9], which can further enhance the capacity of the connected AC grid [9], [10] and renders it particularly appealing from a technological point of view.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the IEEE forecast for 2050 [4] assumes that power systems of the future will combine the advantages of variable frequency AC and DC. Several works have shown that a combination of AC and DC in power systems may bring significant benefits at both transmission and distribution levels [8][9][10][11][12][13]. The advantages of hybrid AC/DC grids include better power flow and nodes voltage control as well as reduced power and voltage losses.…”
Section: Introductionmentioning
confidence: 99%